Tomatidine Suppresses the Destructive Behaviors of Fibroblast-Like Synoviocytes and Ameliorates Type II Collagen-Induced Arthritis in Rats - Yu, Xiaolu; Zhou, Junnan; Zhao, Fuli; Liu, Xuan; Mao, Yuhang; Diao, Li; Wen, Chuanjun; Liu, Mei (Frontiers in Pharmacology, 2021)
Fibroblast-like synoviocytes (FLSs) are the prominent non-immune cells in synovium and play a pivotal role in rheumatoid arthritis (RA) pathogenesis. Searching for natural compounds that may suppress the pathological phenotypes of FLSs is important for the development of RA treatment. Tomatidine (Td), a steroidal alkaloid derived from the solanaceae family, has been reported to have anti-inflammatory, anti-tumor and immunomodulatory effects. However, its effect on RA remains unknown. Here, we examined the inhibitory effect of Td on TNFα-induced arthritic FLSs, and subsequently investigated its therapeutic effect on collagen-induced arthritis (CIA) rats. Our results revealed that Td significantly inhibited TNFα-induced proliferation and migration of arthritic FLSs. In addition, we found that Td treatment could efficaciously ameliorate synovial inflammation and joint destruction of rats with CIA. Both in vitro and in vivo studies showed that Td significantly suppressed the production of pro-inflammatory cytokines including IL-1β, IL-6 and TNFα, and downregulated the expression of MMP-9 and RANKL. Further molecular mechanism studies revealed that the inhibitory effect of Td on RA might attribute to the decreased activations of MAPKs (ERK and JNK) and NF-κB. These findings provide evidence that Td has the potential to be developed into a complementary or alternative agent for RA therapy.